The Chromatin Landscape Channels DNA Double-Strand Breaks to Distinct Repair Pathways - Chen, Zulong; Tyler, Jessica K. (Frontiers in Cell and Developmental Biology, 2022)
DNA double-strand breaks (DSBs), the most deleterious DNA lesions, are primarily repaired by two pathways, namely homologous recombination (HR) and non-homologous end joining (NHEJ), the choice of which is largely dependent on cell cycle phase and the local chromatin landscape. Recent studies have revealed that post-translational modifications on histones play pivotal roles in regulating DSB repair pathways including repair pathway choice. In this review, we present our current understanding of how these DSB repair pathways are employed in various chromatin landscapes to safeguard genomic integrity. We place an emphasis on the impact of different histone post-translational modifications, characteristic of euchromatin or heterochromatin regions, on DSB repair pathway choice. We discuss the potential roles of damage-induced chromatin modifications in the maintenance of genome and epigenome integrity. Finally, we discuss how RNA transcripts from the vicinity of DSBs at actively transcribed regions also regulate DSB repair pathway choice.